Analysis and comparison of innovative large scale thermo-mechanical closed cycle energy storages. (15th June 2022) - Manzoni, Matteo; Patti, Alberto; Maccarini, Simone; Traverso, Alberto
Abstract: In recent years, large installations of renewable power generators have contributed to reduce emissions from fossil sources. Nevertheless, the main features of renewable sources are the unpredictability and the non-dispatchability, exacerbating problems of power balancing for the electrical grid. In such a context, it is essential to investigate innovative energy storage systems, both at small and large scale, to maintain the high quality level of current electrical infrastructure and to guarantee spinning-reserve capability, thus ensuring grid stability. Closed-loop systems for thermo-mechanical energy storage based on rotating machinery could be a solution to achieve this goal. Basing on the state of the art and growing knowledge of CO2 cycles for power production, this paper aims to analyze innovative energy storage solutions involving closed cycles, employing different working fluids in subcritical or supercritical conditions, including CO2, N2 O and SF6 . Moreover, also H2 O was treated as an evolving fluid for benchmark. Such various plant configurations have been sized for a net power level of 10 MWe during charging phase, considering the same charging (compression mode) and discharging (expansion mode) phase duration of 4 h. Their techno-economic features have been compared: Round Trip Efficiency (RTE) greater than 70% is achieved, demonstrating the potential of such plants as utility scale energy storage. Among the different working fluids considered, CO2 in supercritical conditions achieves the best RTE performance. Highlights: Utility-scale energy storage systems to enable further non-dispatchable renewable power production. Carbon dioxide as working fluid for energy storage cycles. Analysis of different working fluids as SF6 and N2 O, in subcritical and supercritical states. Techno-economic comparison of Round Trip Efficiency and dimensions, benchmarked against Adiabatic Compressed Air Energy Storage.